Income diversity of agricultural households in Punjab and its determinants: Evidence from the NSSO surveys - Souradipta Das; Kamal Vatta; Laishram Priscilla (Agricultural Economics Research Review, 2024)
The present study has identified the extent and pattern of income diversification, the factors affecting it, and the impact of income sources on inequality among agricultural households in the state of Punjab. The study has found widespread income inequality among various categories of rural households. The relationship between income diversification and rural household income has pointed towards distress diversification by the relatively poor households. During the period 2002-03 to 2018-19, the semi-medium agricultural households have diversified more. From 2002-03 to 2012-13, the large and small farmers became more specialized, but from 2012-13 to 2018-19, they diversified again. The diversification of rural household income has been found to be significantly influenced by non-farm income, landholding size, and irrigation facilities. The crop income has been found to be inequality inducing and has contributed maximum to income inequality. However, income from livestock, wages, and salaries are found to be viable options for reducing the income inequality.